A novel inhibitor of N6-methyladenosine demethylase FTO induces mRNA methylation and shows anti-cancer activities - Guoyou Xie; Xu-Nian Wu; Yuyi Ling; Yalan Rui; Deyan Wu; Jiawang Zhou; Jiexin Li; Shuibin Lin; Qin Peng; Zigang Li; Hongsheng Wang; Hai-Bin Luo (Elsevier, 2022)
N6-methyladenosine (m6A) modification is critical for mRNA splicing, nuclear export, stability and translation. Fat mass and obesity-associated protein (FTO), the first identified m6A demethylase, is critical for cancer progression. Herein, we developed small-molecule inhibitors of FTO by virtual screening, structural optimization, and bioassay. As a result, two FTO inhibitors namely 18077 and 18097 were identified, which can selectively inhibit demethylase activity of FTO. Specifically, 18097 bound to the active site of FTO and then inhibited cell cycle process and migration of cancer cells. In addition, 18097 reprogrammed the epi-transcriptome of breast cancer cells, particularly for genes related to P53 pathway. 18097 increased the abundance of m6A modification of suppressor of cytokine signaling 1 (SOCS1) mRNA, which recruited IGF2BP1 to increase mRNA stability of SOCS1 and subsequently activated the P53 signaling pathway. Further, 18097 suppressed cellular lipogenesis via downregulation of peroxisome proliferator-activated receptor gamma (PPARγ), CCAAT/enhancer-binding protein alpha (C/EBPα), and C/EBPβ. Animal studies confirmed that 18097 can significantly suppress in vivo growth and lung colonization of breast cancer cells. Collectively, we identified that FTO can work as a potential drug target and the small-molecule inhibitor 18097 can serve as a potential agent against breast cancer.